Pengembangan E-book berbasis Canva "SUPI" tentang Surat-Surat Pendek pada Pembelajaran PAI Kelas 2 SD - Halimah, Ima; Maryanah, Dinah; Nursyifa, Neng Nenden Siti; Aeni, Ani Nur (Borneo Journal of Islamic Education, 2025)
Abstract This study focuses on the development of a Canva-based interactive e-book entitled "SUPI" as a learning medium for short letters in Islamic Religious Education (PAI) for grade 2 Elementary School students. The use of technology in learning is very important to improve students' understanding, especially in religious material. This e-book is designed to help students understand and memorize short letters in a more interesting and interactive way. The development was carried out using the ADDIE model which consists of five stages, namely Analysis (needs analysis), Design (media design), Development (e-book development), Implementation (implementation in learning), and Evaluation (effectiveness evaluation). The results of the study showed that the Canva-based "SUPI" e-book can increase students' learning motivation and involvement in the learning process. In addition, this e-book provides a more enjoyable and effective learning experience than conventional methods. It is hoped that the development of this digital learning media can be an innovative alternative for teachers in teaching PAI material at the elementary school level.